Therapeutic regimens and factors associated with mortality in patients with severe COVID-19 infection treated at the Hospital Nacional Alberto Sabogal Sologuren, 2020 - Llaro-Sánchez, Manuel K (2021)
Objective: To explore the therapeutic regimen and factors associated with mortality in patients with severe COVID-19 infection treated at the Hospital Nacional Alberto Sabogal Sologuren in 2020. Materials and methods: An observational, case-control, analytical and prospective study conducted in patients with severe COVID-19 infection at hospital admission between June and September 2020. The study population was classified into two groups: case group (61 deceased patients) and control group (60 discharged patients). Data were analyzed using Stata statistical software. Bivariate and multivariate logistic regression analyses were performed with a 95 % confidence level. Results: As for patients with severe COVID-19 infection, ages older than 60 years are associated with mortality (p = 0.035; OR = 2.21; CI: [1.05 – 4.63]). Different therapeutic regimens were included in the research: patients who received high-dose methylprednisolone had more probability of dying compared to those who received other corticosteroids (p = 0.001; adjusted OR = 5.18; CI: [1.94 – 13.83]). Patients who were treated with azithromycin for more than five days had more probability of dying compared to those that took it for fewer days (p = 0.000; adjusted OR = 7.14; CI: [2.22 – 22.99]). The multivariate model showed a 73.06 % predictive probability of mortality for patients with severe COVID-19 infection. Conclusions: The therapeutic regimens that include the administration of high-dose methylprednisolone and azithromycin for more than five days increase the probability of dying in patients with severe COVID-19 infection. Furthermore, ages over 60 years were associated with mortality in the patients who participated in the study.